A double blinded comparative study between omega 3 fatty acid infusion versus octreotide infusion in acute pancreatitis - T., Narayanswamy; K., Supreeth; G., Sridhar (International Surgery Journal, 2020)
Background: Over decades the treatment of acute pancreatitis remains debatable with no common consensus on treatment guidelines, with some workers using octreotide infusion and some workers only relying on fluid therapy and symptomatic management. This double blinded comparative trial between omega 3 fatty acid infusion versus octreotide infusion and its response in cases of acute pancreatitis. Methods: This is a study where a double blinded randomised control trial was undertaken in proven cases of acute pancreatitis and patients were given omega 3 fatty acid infusion and octreotide infusion and the observations were documented and followed upon. 50 cases were given omega 3 fatty acid infusion and other 50 were given octreotide infusion and the clinical response, symptomatic improvement was assessed and compared using BISAP and Marshal scoring systems and lipase levels. Results: Omega 3 fatty acid infusion was found to be highly significant as compared to octreotide in cases of acute pancreatitis in terms of clinical improvement, reduced hospital stay, and SIRS. Conclusions: Omega 3 fatty acid infusion is the future in cases of acute pancreatitis which is cheap and easily available with no side effects and reduces the morbidity and mortality in acute pancreatitis with reduced hospital stay in turn resulting in overall reduced medical expenditure.